Oil Sparks in the Amazon Local Conflicts, Indigenous Populations, and Natural Resources - Vasquez, Patricia I. (Studies in Security and International Affairs, 2014)
For decades, studies of oil-related conflicts have focused on the effects of natural resource mismanagement, with the attendant economic booms and busts, or clashes between rebels and ruling governments over hydrocarbon resources. In Oil Sparks in the Amazon, Patricia I. Vásquez writes that while oil busts and civil wars are common, the tension over oil in the Amazon has played out in ways inextricable from the region itself. Oil disputes in the Amazon primarily involve local indigenous populations. These groups' social and cultural identities differ from the rest of the population, and the diverse disputes over land, displacement, water contamination, jobs, and wealth distribution reflect those differences. Vásquez's conflict analyses, and her recommendations to resolve or prevent them, are based on fifteen years of travel to the oil-producing regions of Latin America, and hundreds of interviews with the stakeholders in local conflicts.